Novel Structurally Designed Vaccine for S. aureus α-Hemolysin: Protection against Bacteremia and Pneumonia - Adhikari, Rajan P. (Public Library of Science, 2012)
Staphylococcus aureus (S. aureus) is a human pathogen associated with skin and soft tissue infections (SSTI) and life threatening sepsis and pneumonia. Efforts to develop effective vaccines against S. aureus have been largely unsuccessful, in part due to the variety of virulence factors produced by this organism. S. aureus alpha-hemolysin (Hla) is a pore-forming toxin expressed by most S. aureus strains and reported to play a key role in the pathogenesis of SSTI and pneumonia. Here we report a novel recombinant subunit vaccine candidate for Hla, rationally designed based on the heptameric crystal structure. This vaccine candidate, denoted AT-62aa, was tested in pneumonia and bacteremia infection models using S. aureus strain Newman and the pandemic strain USA300 (LAC). Significant protection from lethal bacteremia/sepsis and pneumonia was observed upon vaccination with AT-62aa along with a Glucopyranosyl Lipid Adjuvant-Stable Emulsion (GLA-SE) that is currently in clinical trials. Passive transfer of rabbit immunoglobulin against AT-62aa (AT62-IgG) protected mice against intraperitoneal and intranasal challenge with USA300 and produced significant reduction in bacterial burden in blood, spleen, kidney, and lungs. Our Hla-based vaccine is the first to be reported to reduce bacterial dissemination and to provide protection in a sepsis model of S. aureus infection. AT62-IgG and sera from vaccinated mice effectively neutralized the toxin in vitro and AT62-IgG inhibited the formation of Hla heptamers, suggesting antibody-mediated neutralization as the primary mechanism of action. This remarkable efficacy makes this Hla-based vaccine a prime candidate for inclusion in future multivalent S. aureus vaccine. Furthermore, identification of protective epitopes within AT-62aa could lead to novel immunotherapy for S. aureus infection.